Dancing in the Dust Noguchi, Graham, Cunningham: preservation politics - Siegel, Marcia B. (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Noguchi, Graham, Cunningham: preservation politics. Graham filmed many of her early dances, but those films were like malevolent spirits, consulted for their magic information and then hidden away again. Noguchi was just as interested in spirituality, sexuality and the psyche as Graham; they were friends and fellow-seekers as well. When they weren't actually worn on the dancers' bodies, Noguchi's objects served as monumental framing pieces, emblematic backgrounds and platforms, signposts for the dance's metaphorical journey. I enjoy the immediacy of Cunningham's dancers' performing, the opportunity to examine everything with new eyes, his resistance to stagnation and banality. PALABRAS CLAVE: Martha Graham, Isamu Noguchi, Space of the Mind, filmed dance, Robert Tracy, Night Journey, Cave of the Heart, Yuriko Kimura, Merce Cuningham, Summerspace, Interspace, BIPED, Way Station, RainForest.
Spaces of the Mind. Isamu Noguchi's Dance Designs, Robert Tracy. Proscenium Publishers, 2000.